2014
DOI: 10.1111/all.12535
|View full text |Cite
|
Sign up to set email alerts
|

Stat5 gene dosage in T cells modulates CD8+T-cell homeostasis and attenuates contact hypersensitivity response in mice

Abstract: Our data identify Stat5 as a dose-dependent regulator of CD8(+) T-cell functions in contact allergies and suggest that modulation of Stat5 dosage could be used to target contact allergies in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
3
5
0
Order By: Relevance
“…Thus, the differences in b-catenin expression levels in the same mouse model can either result in the block of T cell development at the DP stage, causing a predisposition to leukemia (33), or they can initiate the development of an autoimmune/inflammatory disease in the CNS (as in the current study). Although both models showed a survival These data highlight the previously reported importance of b-catenin expression levels for its biological activity (32,47), which has also been observed for other transcription factors (48,49).…”
Section: Discussionsupporting
confidence: 81%
“…Thus, the differences in b-catenin expression levels in the same mouse model can either result in the block of T cell development at the DP stage, causing a predisposition to leukemia (33), or they can initiate the development of an autoimmune/inflammatory disease in the CNS (as in the current study). Although both models showed a survival These data highlight the previously reported importance of b-catenin expression levels for its biological activity (32,47), which has also been observed for other transcription factors (48,49).…”
Section: Discussionsupporting
confidence: 81%
“…Despite the Vav1 promoter–dependent expression of hSTAT5B N642H throughout the entire hematopoietic system, malignancy evolved in CD8 + T cells. This development could be a result of the CD8 + T cell sensitivity to the Stat5a/b gene dosage that was described previously in mice ( 62 ). Moreover, it has been reported that CD8 + T cells are more susceptible to oncogenic drivers, especially when these drivers are activated by cytokines or triggered via T cell receptors ( 62 , 63 ).…”
Section: Discussionsupporting
confidence: 56%
“…The idea that STAT5 concentration can impact cellular function also has precedent. Of particular interest are studies reporting severe immunological phenotypes in transgenic mice which over-express STAT5A or STAT5B ( Kelly et al, 2003a ; Kelly et al, 2003b ), and studies showing that Stat5a/b haplo-insufficiency ameliorates contact hypersensitivity ( Nivarthi et al, 2014 ). In addition, we have previously demonstrated that ectopic STAT5A can expand the target repertoire of STAT5 in mouse embryonic fibroblasts ( Zhu et al, 2012 ), and have explored the concept of STAT5 gene dosage in the context of mammary development, finding that a high STAT5 threshold must be reached for mammary epithelial cell differentiation ( Yamaji et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%